Molecular Characterisation of Lactobacillus Plantarium Isolated from Malaysian Fermented Foods (Tempeh and Tempoyak) - Mat Issa @ Zakaria, Zuraini (2002)
Ten and fifteen strains of Lactobacillus plantarum were isolated from tempeh and tempoyak, respectively. The identity of these isolates was confirmed with API 50 CHL kit and the polymerase chain reaction (PCR) using a pair of specific primers. All strains were resistant towards nalidixic acid. kanamycin, gentamycin, streptomycin, bacitracin, moxalaactam norfloxacin and, vancomycin. 9, 22, 19, 22 and 22 strains of L. plantarum were resistant against penicillin, cefuroxime, tetracycline, cephalothin and ceftazidime, respectively. Six (60%) and 13 (86.7%) strains of L. plantarum isolated from tempeh and tempoyak, respectively harboured small plasmid DNA ranging in size from 4.7 to 1.2 MDa, and 10 (40%) of these strains were harboured two plasmids. These strains could be grouped into 13 groups based on the size and number of plasmid DNA. Different random amplified polymorphic DNA (RAPD)pattern was obtained when the DNA of these strains were amplified with four 10-mer primers that known as GEN1-50-05, GEN1-50-06, GEN1-50-07 and GEN1-50-08. The strains were separated into 7 clusters in a constructed dendrogram at low similarity index (0.15 to 0.42). The whole cell protein profiles of 14 representatives L. plantarum strains were obtained using sodium dodecyl sulphate-polyacylamide gel electrophoresis (SDS-PAGE) and analysed with the Gelcompar Version 4.1 (Applied Maths, Kortrijk, Belgium). These strains have almost the sam.. number of protein bands ranging in size from 34.7 to 100 kilodalton (kDa). The whole cell protein profiles demonstrated intra-species differences and enabled to separate three distinct clusters of L. plantarum at 84% similarity. A dendrogram of L. plantarum strains was obtained by the unweighted average pair group matrix analysis of correlation values. Twelve strains were grouped into three main clusters and two strains were separated. The whole cell proteins of ten strains were resolved into 13 bands and 12 bands were resolved from two strains, whereas the other two strains were exhibited 11 and 14 bands, respectively. Among the characterization techniques used, RAPD has been concluded as the best, rapid and reproducible tool in characterising the L. plantarum strains isolated from tempeh and tempoyak.